Biomaterials-mediated CRISPR/Cas9 delivery: recent challenges and opportunities in gene therapy - Dubey, Ankit Kumar; Mostafavi, Ebrahim (Frontiers in Chemistry, 2023)
The use of biomaterials in delivering CRISPR/Cas9 for gene therapy in infectious diseases holds tremendous potential. This innovative approach combines the advantages of CRISPR/Cas9 with the protective properties of biomaterials, enabling accurate and efficient gene editing while enhancing safety. Biomaterials play a vital role in shielding CRISPR/Cas9 components, such as lipid nanoparticles or viral vectors, from immunological processes and degradation, extending their effectiveness. By utilizing the flexibility of biomaterials, tailored systems can be designed to address specific genetic diseases, paving the way for personalized therapeutics. Furthermore, this delivery method offers promising avenues in combating viral illnesses by precisely modifying pathogen genomes, and reducing their pathogenicity. Biomaterials facilitate site-specific gene modifications, ensuring effective delivery to infected cells while minimizing off-target effects. However, challenges remain, including optimizing delivery efficiency, reducing off-target effects, ensuring long-term safety, and establishing scalable production techniques. Thorough research, pre-clinical investigations, and rigorous safety evaluations are imperative for successful translation from the laboratory to clinical applications. In this review, we discussed how CRISPR/Cas9 delivery using biomaterials revolutionizes gene therapy and infectious disease treatment, offering precise and safe editing capabilities with the potential to significantly improve human health and quality of life.